The Effects of 5-Hydroxytryptophan in Combination with Different Fatty Acids on Gastrointestinal Functions: A Pilot Experiment. (19th August 2014) - Sauer, Helene; Mack, Isabelle; Kohler, Silke; Siegle, Stefanie; Rieber, Nicole; Zipfel, Stephan; Otto, Bärbel; Ritze, Yvonne; Bischoff, Stephan C.; Enck, Paul
Abstract : Background. Fat affects gastric emptying (GE). 5-Hydroxythryptophan (5-HTP) is involved in central and peripheral satiety mechanisms. Influence of 5-HTP in addition to saturated or monounsaturated fatty acids (FA) on GE and hormone release was investigated. Subjects/Methods. 24 healthy individuals (12f : 12m, 22–29 years, BMI 19–25.7 kg/m²) were tested on 4 days with either 5-HTP + short-chain saturated FA (butter), placebo + butter, 5-HTP + monounsaturated FA (olive oil), or placebo + olive oil in double-blinded randomized order. Two hours after FA/5-HTP or placebo intake, a 13 C octanoid acid test was conducted. Cortisol, serotonin, cholecystokinin (CCK), and ghrelin were measured, as were mood and GE. Results. GE was delayed with butter and was normal with olive (P < 0.05 ) but not affected by 5-HTP. 5-HTP supplementation did not affect serotonin levels. Food intake increased plasma CCK (F = 6.136 ; P < 0.05 ) irrespective of the FA. Ghrelin levels significantly decreased with oil/5-HTP (F = 9.166 ; P < 0.001 ). The diurnal cortisol profile was unaffected by FA or 5-HTP, as were ratings of mood, hunger, and stool urgency. Conclusion. Diverse FAs have different effects on GE and secretion of orexigenic and anorexigenic hormones. Supplementation of 5-HTP had no effect on plasma serotonin and central functions. Further studies are needed to explain the complex interplay.